Primary health care quality in Iran: a systematic review and meta-analysis - Gorji, Hasan Abolghasem; Royani, Sanaz; Mohseni, Mohammad; Azami-Aghdash, Saber; Moosavi, Ahmad; Sheyklo, Sepideh Gareh (Family Medicine & Primary Care Review, 2019)
Quality measurement is the first step in improving overall quality. Servqual has been identified as one of the most important methods frequently used in assessing the quality of healthcare services. This study aims to systematically review and conduct meta- analysis of conducted studies in this regard in which Servqual tools were used to assess and measure the quality of services. In this systematic review and meta-analysis, the required data were collected using several keywords (and their Persian equivalents): services quality, Servqual, quality, gap, primary health cares, health services, Iran. The databases searched were as follows: PubMed, Scopus, Google Scholar, SID, Magiran, and Iranmedex. The comprehensive meta-analysis (CMA) software, Version 2 was used for data analysis. Based on the random effect model, the total mean score of Service Consumers’ perception, Service Consumers’ expectation and the gap between them were estimated as being 3.81 (95% CI: 3.56–4.06), 4.49 (95% CI: 4.31–4.67) and -0.83 (95% CI: -065 – -1.01), respectively. The lowest score of consumers’ perception of services quality, was related to the empathy dimension (3.57) and the highest score of consumers’ expectation of services quality was related to the reliability dimension (4.60). Furthermore, there was a quality gap in all dimensions. In order to achieve desired quality and meet service receivers’ needs, attention should be always given to their views, so that proper planning can be done to address existing problems through assessing views. Should such be undertaken, we would be able to witness services quality improvement.